If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + 1) = 3(1 + 5x) Reorder the terms: 3(1 + 5x) = 3(1 + 5x) (1 * 3 + 5x * 3) = 3(1 + 5x) (3 + 15x) = 3(1 + 5x) 3 + 15x = (1 * 3 + 5x * 3) 3 + 15x = (3 + 15x) Add '-3' to each side of the equation. 3 + -3 + 15x = 3 + -3 + 15x Combine like terms: 3 + -3 = 0 0 + 15x = 3 + -3 + 15x 15x = 3 + -3 + 15x Combine like terms: 3 + -3 = 0 15x = 0 + 15x 15x = 15x Add '-15x' to each side of the equation. 15x + -15x = 15x + -15x Combine like terms: 15x + -15x = 0 0 = 15x + -15x Combine like terms: 15x + -15x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5f-13=-7 | | 5n-9=2 | | 12z+4=2[5z+8]-12 | | -6ysinx=0 | | 4t+5=53 | | -2(3t+6)= | | 5n-9=-2 | | 4x-11=n+26 | | 2n-22=14-4n | | 4s-15=4s+11 | | 6x-5=12+1 | | v-6.39=8.53 | | 2X+4(3X-7)=112 | | 20+9w=4(15-w) | | 3y-5+2y=5 | | 2x+4y=40-16 | | (36a-6)=(4-24a) | | 7XY= | | x+2x=243 | | 4x+2y=40-16 | | Y=0.25x+3 | | -8pr+8q-10r+10=5q-5r+9 | | 2(x-4)+3=15 | | 4x+8=4(x+7) | | 6x+7x-x= | | 4d-16=20 | | 4x^2-10x+12=9x | | 5(x+7)=3(x+8) | | (4x+8)+(3x+2)= | | 10x-23=29-3 | | (3x-4y^2)(9x^2+12xy^2+16y^4)= | | -1=4x-(3x-9)+-(-2x+8) |